EDUCATION AS EPISTEMOLOGICAL RESISTANCE: DECONSTRUCTION OF WESTERN HEGEMONY IN THE POLITICAL-EDUCATIONAL THOUGHT OF ALI KHAMENEI - Ali Ridho Imansyah (Sadra International Institute, 2026)
The dominance of the Western educational paradigm in the era of globalization has functioned as a form of epistemological colonization that marginalizes indigenous knowledge systems and Islamic spirituality through the supremacy of secularism, materialism, and cultural hegemony. This condition poses serious challenges to the intellectual sovereignty of the Muslim world, particularly in preserving its epistemological identity. This study aims to analyze the political-educational thought of Sayyid Ali Khamenei concerning education as an instrument of epistemological resistance against Western domination. The research employs a qualitative library-based method using descriptive-analytical and philosophical hermeneutic approaches. Primary sources include official speeches, major written works of Khamenei, and Iranian educational policy documents from 1989 to 2024. The theoretical framework applies Antonio Gramsci’s theory of cultural hegemony, Louis Althusser’s concept of Ideological State Apparatus, and postcolonial educational theory. The findings reveal that Khamenei’s epistemological resistance is constructed through three interconnected layers: identity strengthening through tarbiyah, scientific independence through the concept of Jihād-e ‘Ilmī, and cultural filtering to prevent Western epistemological infiltration. These dimensions form an integrated educational framework positioning education as a long-term political strategy toward genuine independence (istiqlāl). In conclusion, within Khamenei’s thought, education serves as a strategic instrument of epistemological decolonization that integrates knowledge, morality, and spirituality into a comprehensive project of resistance against Western global hegemony.